Oil Palm Plantation Expansion: An Overview of Social and Ecological Impacts in Indonesia - Dadi Dadi (Budapest International Research and Critics University, 2021)
This study aims to analyze the extent of land clearing and the role of farmers in land expansion, besides that this study aims to identify the social and ecological impacts caused by land clearing. The method used is descriptive qualitative with primary data collection techniques in the form of interviews and FGD with farmers and related stakeholders, secondary in the form of land cover recording using Landsat 8 TM imagery. The results showed that both private companies, plasma farmers and independent smallholders had a role in land expansion, but private companies were dominant in primary forest expansion. The social impact caused by the conflict between transmigrants (immigrants) and indigenous Malays (natives) triggered by social jealousy and concerns about the loss of Malay descendants caused by the dominance of migrant tribes. Ecological impacts in the form of reduced carbon stocks, deforestation, forest fires and loss of biodiversity. The social impact caused by the conflict between transmigrants (immigrants) and indigenous Malays (natives) triggered by social jealousy and concerns about the loss of Malay descendants caused by the dominance of migrant tribes. Ecological impacts in the form of reduced carbon stocks, deforestation, forest fires and loss of biodiversity. The social impact caused by the conflict between transmigrants (immigrants) and indigenous Malays (natives) triggered by social jealousy and concerns about the loss of Malay descendants caused by the dominance of migrant tribes. Ecological impacts in the form of reduced carbon stocks, deforestation, forest fires and loss of biodiversity.